Discourse-pragmatic variation across situations, varieties, ages: i don't know in sociolinguistic and medical interviews. (July 2016) - Pichler, Heike; Hesson, Ashley
Abstract: Our analysis ofi don't know (IDK) variability in four sub-corpora of sociolinguistic and mental health interviews clarifies the context-dependency of discourse-pragmatic variation, and demonstrates the translational potential of socially responsible, linguistic research. Systematic and accountable analysis of over 700 tokens of IDK in these data reveals that while IDK variants, functions and syntactic configurations are differentially distributed across situation, variety and age, form-function correlations in IDK use are robust across these parameters. These results demonstrate that discourse-pragmatic variables such as IDK retain some probabilistic relationships that aid in consistent interpretation across contexts of use, while other aspects of variability are used in stylistically distinct ways across e.g. situations and social groups. Moreover, our analysis of IDK in mental health interviews shows how the variationist analysis of site-particular communicative practices can uncover language variation patterns that have the potential to affect practice, research and teaching outside of the sociolinguistics community. Highlights: Comparative analysis of I DON'T KNOW (IDK) in medical & sociolinguistic interviews. 700+ tokens studied with qualitative & quantitative variationist methods. Significant intra- & inter-context differences in IDK use (form, function, syntax). Form ( I don't know v. I dunno ) and function (cognitive v. other) correlation robust. Possible applications for improving doctor-patient communication in mental health settings.